The Doha Round: "death-defying agenda" or "don't do it again"? - Stuart Harbinson (European Centre for International Political Economy (ECIPE), 2009)
Almost eight years after the launch of the Doha Round, the WTO negotiations remain mired in a swamp of detail, with many participants unwilling or unable to make the hard decisions which would bring the Round to a conclusion. Meanwhile, the world has changed dramatically with the onset of a global economic crisis of proportions seldom, if ever, seen before. This has radically changed the context within which the Round is placed and may lead to fundamental rethinking of its future. This paper examines the origins of the Round and concludes that, at the time, its launch was well-founded. It traces the twists and turns in the negotiations since then and finds that, while progress has been incremental, it has also been painfully slow. Decisive action has been avoided. It addresses three issues: whether, in current economic circumstances and given the long but inconclusive history of the negotiations, it is important to complete the Doha Round and if so, how this could be achieved; whether there are alternative approaches to WTO negotiations that could be explored for the future; and what a future negotiating agenda might look like. It concludes with some reflections on the prospects for the WTO at the present juncture in its short history.
Keywords: F10; F13; F51; F55; F59; 330; World Trade Organisation; Doha Round; Multilateral Trade Policy; International Institutions and Negotiations; WTO-Recht; Verhandlungen; Internationale Handelspolitik; Handelsliberalisierung; Internationale Wirtschaftsbeziehungen